Effect of sowing time on the realization of productivity potential of modern varieties of soft winter wheat in the context of climate change - О. Л. Уліч (Plant Varieties Studying and Protection)
The effect of sowing time on realization of the natural productivity potential of modern soft winter wheat varieties was studied. It is established that the use of current agricultural technologies in a context of climate change has caused shift of calendar sowing terms to the second half of the optimal terms comparing with earlier cultivated varieties. In subzones of Kirovohrad and Bila Tserkva state variety testing stations the highest yield of winter wheat is formed in case of sowing on September 20–30, but the optimum for Kirovohrad station fall on September 30, Bila Tserkva station – on September 20 and 30. Sowing in earlier or later time leads to decreasing yields, especially of Vynnychanka, Smuhlyanka, Zolotokolosa and Tripilska varieties. Bogdana and Kuialnyk varieties are the most adaptive to sowing time under agroecological conditions of Kirovohrad state variety testing station.